2021
DOI: 10.3390/nu13114017
|View full text |Cite
|
Sign up to set email alerts
|

Six Oligosaccharides’ Variation in Breast Milk: A Study in South China from 0 to 400 Days Postpartum

Abstract: This study investigated the variation in oligosaccharide levels in the breast milk of south Chinese mothers in a prolonged breastfeeding period of up to 400 days postpartum. A total of 488 breast milk samples were collected from 335 healthy mothers at five different time points: 0–5 days, 10–15 days, 40–45 days, 200–240 days, and 300–400 days postpartum. A high-performance anion-exchange chromatography-pulsed amperometric detector (HPAEC-PAD) was used to quantify 2′-fucosyllactose (2′-FL), 3-fucosyllactose (3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 53 publications
(83 reference statements)
4
18
0
Order By: Relevance
“…The concentrations of HMO in breast milk vary significantly between mothers, as well as for stages of lactation and maternal Lewis secretor status [ 17 ]. The concentrations of the HMO, 2′-fucosyllacose (2′-FL) at 1 g/L and lacto-N-neotetraose (LNnT) at 0.5 g/L in the study formula were chosen from within the range of observed breast milk concentrations [ 18 ]. A recent trial in infants with CMPA fed an EHF supplemented with 2′-FL and LNnT suggested a protective effect against respiratory and ear infections [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The concentrations of HMO in breast milk vary significantly between mothers, as well as for stages of lactation and maternal Lewis secretor status [ 17 ]. The concentrations of the HMO, 2′-fucosyllacose (2′-FL) at 1 g/L and lacto-N-neotetraose (LNnT) at 0.5 g/L in the study formula were chosen from within the range of observed breast milk concentrations [ 18 ]. A recent trial in infants with CMPA fed an EHF supplemented with 2′-FL and LNnT suggested a protective effect against respiratory and ear infections [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Beneficial effects of HMO include the reduction in glycan-dependent viral infections (e.g., rotavirus), as well as an increased production of short-chain fatty acids (SCFA) by bifidobacteria, which create an acidic gut environment and protect from invasive enteropathogens [ 3 , 14 , 41 ]. The main HMO species in the breast milk of secretor mothers is 2′-FL, and it persists at levels of around 1g/L until about 12 months of age [ 18 ]. The test formula contained similar amounts of 2′-FL, and an anti-infective effect comparable to that seen in breastfed infants thus appears plausible.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, the gut microbiome of infants of nonsecretor mothers is low in bifidobacteria due to low levels of 2′-FL in breast milk, which may provide lower levels of biological protection against infections [ 17 ]. HMO levels in breast milk gradually decrease during lactation, however, in secretor mothers, significant levels of 2′-FL persist until at least 12 months after delivery [ 18 ]. Recently, 2′-FL and lacto-N-neotetraose (LNnT) became novel ingredients in infant formulas [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The concentration of HMOs in breast milk can be influenced by many factors, including the lactation period, maternal phenotypes, gestational age, a lactating diet, maternal anthropometric parameters (e.g., parity, age, and prepregnancy BMI), and ethnicity. Previous research investigated the effect of the lactation period and maternal phenotypes on the level of HMOs and demonstrated the variation of HMOs in different lactation stages and milk groups that were based on maternal phenotype. , The total concentration of HMOs decreased gradually during the stages of lactation. The content ranged from 20 to 25 g/L in the colostrum and 5 to 15 g/L in mature milk.…”
Section: Hmos Structure Concentration and Functionmentioning
confidence: 99%